The Mongols & the Islamic world from conquest to conversion - Jackson, Peter (Yale University Press, 2017)
Distinguished historian Peter Jackson offers a fresh and fascinating consideration of the years of infidel Mongol rule in Western Asia, drawing from an impressive array of primary sources as well as modern studies to demonstrate how Islam not only survived the savagery of the conquest, but spread throughout the empire.